2018
DOI: 10.1002/pra2.2018.14505501033
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the impact of a virtual reality workstation in an academic library: Methodology and preliminary findings

Abstract: Collections of 3D models and the analytic affordances of virtual reality (VR) systems can be integrated to form a “3D digital heritage ecosystem” (Limp, et al., 2011), providing a potentially richer and more intuitive learning environment that enables students to interact with models of artifacts and spaces that are too rare, fragile, or distant to access directly. This paper describes efforts to evaluate the impact of virtual reality on undergraduate instruction in varied disciplines, hosted within an academi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…Current headset hardware effectively combines these affordances and thereby engenders measurable efficiencies when it comes to analyzing complex 3D data . Importantly, these benefits extend across disciplines and levels of expertise, and fields ranging from archaeology to architecture, and civil engineering to medicine, have effectively leveraged these affordances to improve performance. VR has also proven useful outside of controlled laboratory conditions, and an increasing number of instructors (at all levels) are adopting these tools to better help achieve learning outcomes through the use of virtual field trips, distributed architectural critiques, and easy access to heretofore archived or otherwise inaccessible course content. …”
Section: Introductionmentioning
confidence: 99%
“…Current headset hardware effectively combines these affordances and thereby engenders measurable efficiencies when it comes to analyzing complex 3D data . Importantly, these benefits extend across disciplines and levels of expertise, and fields ranging from archaeology to architecture, and civil engineering to medicine, have effectively leveraged these affordances to improve performance. VR has also proven useful outside of controlled laboratory conditions, and an increasing number of instructors (at all levels) are adopting these tools to better help achieve learning outcomes through the use of virtual field trips, distributed architectural critiques, and easy access to heretofore archived or otherwise inaccessible course content. …”
Section: Introductionmentioning
confidence: 99%
“…As an alternative, experimental classrooms have integrated single (or small sets of) learning objects from existing 3 D asset repositories, like Morphosource, Sketchfab,\ or the NIH 3 D Print Exchange and others; micro-experiences that make use of existing or easily produced contents, which might lack the sort of gamification or other functionality that students have come to expect of what is perceived as videogame technology (Lischer‐Katz et al , 2018; Dede et al , 2017; Greene and Groenendyk, 2019; Jang et al , 2017) [1]. These targeted integrations are supported by a small number of versatile “productivity-grade” XR applications – open ended sandboxes where data from any field can quickly enter and exit the virtual world, regardless whether that data represents a design idea, abstract data visualization or real-world object or specimen (Mills, 2020; Cook and Lischer-Katz, 2021).…”
Section: Part 2: Practical and Technological Considerations Shaping Educational Xrmentioning
confidence: 99%
“…Academic libraries have provided support and education about virtual reality by the form of credentialing programs, play-based experiences such as game development competitions, and integrations with curriculum in disciplines as diverse as art history, anthropology, biochemistry, computer science, and more (Nichols et al 2017;Patterson et al 2019;Lischer-Katz, Cook, and Boulden 2018;Hahn 2018). The University of Oklahoma Library, which has a very comprehensive virtual reality program, conducted student evaluations in some of these classes, demonstrating that VR assignments had a positive impact on learning (Cook and Lischer-Katz 2019;Lischer-Katz, Cook, and Boulden 2018). Some librarians have even suggested that virtual reality would be an appropriate medium for information literacy instruction (Smith 2019).…”
Section: Introductionmentioning
confidence: 99%